2016
DOI: 10.1074/jbc.m115.712380
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-driven Myosin II Mediates the Pro-fibrotic Fibroblast Phenotype

Abstract: Pro-fibrotic mesenchymal cells are known to be the key effector cells of fibroproliferative disease, but the specific matrix signals and the induced cellular responses that drive the fibrogenic phenotype remain to be elucidated. The key mediators of the fibroblast fibrogenic phenotype were characterized using a novel assay system that measures fibroblast behavior in response to actual normal and fibrotic lung tissue. Using this system, we demonstrate that normal lung promotes fibroblast motility and polarizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 57 publications
(53 reference statements)
3
64
0
2
Order By: Relevance
“…Myosin II acts as an actin crosslinker (41) whereas myosin VI acts as a mediator protein, which binds cadherin to actin filaments (42). Loss of myosin II selectively inhibits myofibroblast differentiation in fibroblasts of fibrotic lung when compared to healthy phenotype (43). From our current findings and previous results from others, we speculate that (…”
Section: Discussionsupporting
confidence: 76%
“…Myosin II acts as an actin crosslinker (41) whereas myosin VI acts as a mediator protein, which binds cadherin to actin filaments (42). Loss of myosin II selectively inhibits myofibroblast differentiation in fibroblasts of fibrotic lung when compared to healthy phenotype (43). From our current findings and previous results from others, we speculate that (…”
Section: Discussionsupporting
confidence: 76%
“…Importantly, we observed that the percentage of αSMA + AoAFs present in 5 wt% hydrogels tracked with hydrogel modulus (Pearson's correlation, r = 0.6677, p = 0.0192; Table S4, Supporting Information), similar to the effects observed during pathologic tissue stiffening in vivo. [ 22 ] Conversely, the percentage of αSMA + AoAFs was not altered over time in 7.5 and 10 wt% hydrogels, where ≈20% of AoAFs in 7.5 wt% hydrogels and ≈45% of AoAFs in 10 wt% hydrogels expressed diffuse αSMA staining after 42 days in culture, similar to day 1. Unlike the 5 wt% hydrogels, the percentage of αSMA + AoAFs did not correlate with bulk shear moduli in 7.5 and 10 wt% hydrogels (Table S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 95%
“…On the other hand, ≈50% of AoAFs in the stiffer 10 wt% hydrogels expressed diffuse αSMA staining after 24 h. While our results differ from previous observations in 3D hydrogels, where fibroblast activation decreased with increased stiffness, [ 21 ] they are consistent with in vivo observations of pathologic tissue stiffening driving myofibroblast transdifferentiation. [ 22 ] Further, αSMA expression in 10 wt% hydrogels was accompanied by the secretion of the inflammatory proteins, IL‐6, and MCP‐1 (measured via ELISA; Figure S5B,C, Supporting Information). Interestingly, significantly increased IL‐6 and MCP‐1 production by AoAFs encapsulated in 5 wt% hydrogels, compared to 7.5 wt% hydrogels, suggests that inflammatory cytokine production by activated AoAFs may be regulated through pathways distinct from those driving myofibroblast transdifferentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Crosslinking of the ECM by enzyme-and/or nonenzyme-dependent mechanisms stiffens the ECM (2). Matrix stiffening in the lung has been identified as a critical factor that perpetuates/amplifies pulmonary fibrosis (3)(4)(5)(6)(7)(8)(9)(10)(11). Understanding the mechanisms by which matrix stiffness regulates fibrotic lung progression will provide new interventions and therapeutic approaches to prevent, treat, and potentially reverse pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%